The Comic-Based E-Worksheets on The Human Digestive System Material : Engslih - Okky Putra Begawan Tubagus; Mahardika, I Ketut; Budiarso, Aris Singgih (International Journal of Educational Sciences and Development, 2023)
The purpose of this study is to investigate the validity of a comic based e-worksheets on human digestive system material in order to improve the collaborative abilities of grade VIII junior high school students. The research method used is development research, sometimes known as R&D. The ADDIE development model is applied, and it consists of five stages: analyze, design, development, implementation, and evaluation. Which of the five phases is used to test the validity of comic based e-worksheets is limited to three stages or up to the stage development. A validation questionnaire sent to three validation experts served as the study tool. Based on the validation data, we received an average score of 84% with a valid category.